Determinants of Postpartum Depression among Mothers at the Kassi-Kassi Community Health Center - Djunaidi, RasyifWildan; Jelita Inayah Sari; Abd. Rahman; Veraferial Muchtar; Mardan (Universitas Islam Negeri Alauddin Makassar, 2026)
Background: Postpartum depression (PPD) affects approximately one in seven postpartum mothers and may lead to serious complications, including impaired child growth, psychotic disorders, and infanticide if left untreated. Data regarding PPD and its associated factors in South Sulawesi Province remain limited. Objective: This study aimed to determine the relationship between maternal age, occupation, family income, education level, and religiosity among mothers with postpartum depression. Methods: This study used a quantitative cross-sectional design. A total of 62 postpartum mothers were selected using a random sampling technique. Data were analyzed using univariate and bivariate analysis. The chi-square test was applied to assess the relationship between independent variables and postpartum depression. Results: The analysis showed a significant relationship between maternal age and postpartum depression (p = 0.048). Religiosity was also significantly associated with postpartum depression (p = 0.037). No significant relationship was found between family income and postpartum depression (p = 0.731) or between education level and postpartum depression (p = 0.620). Conclusion: Maternal age and religiosity were significantly associated with postpartum depression, while education level and family income showed no significant association.